A drink before suicide: analysis of the Queensland Suicide Register in Australia. (2020) - Kõlves, Kairi; Koo, Yu Wen; de Leo, Diego
Abstract: Aims: Previous studies analysing blood alcohol concentration (BAC) at the time of suicide have primarily focused on sociodemographic factors. Limited research has focused on psychosocial factors and co-ingestion of other substances to understand the mechanisms of how alcohol contributes to death by suicide. The aim was to examine time trends, psychosocial factors related to acute alcohol use and co-ingestion of alcohol and other substances before suicide. Methods: The Queensland Suicide Register in 2004–2015 was utilised and analysed in 2019. The cut-off point for positive BAC was set at ⩾0.05 g/dl. Substances were categorised as medicines, illegal drugs and other. Medicines were coded by the Anatomical Therapeutic Chemical (ATC) classification system. Joinpoint regression, univariate odds ratios, age and sex-adjusted odds ratios and Forward Stepwise logistic regression were performed. Results: BAC information was available for 6744 suicides, 92% of all cases in 2004–2015. The final model showed that independent factors distinguishing BAC+ from BAC− were: age group 25–44 years, Australian Indigenous background, being separated or divorced, hanging, diagnosis of substance use, lifetime suicidal ideation, relationship and interpersonal conflict, not having psychotic and other psychiatric disorder, and no nervous system drugs or any other substances in blood at the time of suicide. Conclusions: Our findings suggest that people who die by suicide while under the influence of alcohol are more likely to be under acute stress (e.g. separation) and not have earlier psychiatric conditions, except substance use. This highlights the importance of more strict alcohol policies, but also the need to improve substance use treatment.